Translation and validation of the Sociocultural Attitudes Towards Appearance Questionnaire-4 in Iranian adolescents - Amiri, Sohrab; Navab, Amir Ghasemi (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2018)
The goal of this research was to validate the Sociocultural Attitudes Towards Appearance Questionnaire-4 (SATAQ-4) in the adolescent population. For this purpose, 662 male adolescents were selected, then SATAQ-4 (Schaefer et al. 2015), Body Appreciation, Appearance Evaluation, Body Surveillance and Acceptance, and Action Questionnaire-II (AAQ-II) were distributed among them. The reliability was assessed by α coefficient, test-retest, and split-half coefficient, and the validity was assessed with other questionnaires to determine the psychometric properties of SATAQ-4. The confirmatory factor structure was assessed by confirmatory factor analysis. Factor analysis indicated that SATAQ-4 has five factors, and checking the validity of the inventory using Cronbach’s α, test-retest, and split-half coefficient reflected the stability of the scale; the criterion validity of the SATAQ-4 with other questionnaires showed desirable discriminant and convergence validity. Overall, the findings indicated that SATAQ-4 has good psychometric properties in the adolescent population, and the tool can be used in studies in the general population. However, it seems that the SATAQ-4 subscales have low internal consistency in the Iranian adolescent population in comparison with the original version.